Position of Resolving Human Rights Violations through The Truth and Reconciliation Commission (TRC) Mechanism in Indonesia - Nora Liana; Ricky Rosiwa; Ahmad Mulia Sembiring; Dona Popou Saragih; Ade Ira Octa Femi; Malahayati (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Resolving human rights violations in Indonesia is a complex issue, considering the many cases of violations that occurred during the conflict, especially during the New Order period. One of the mechanisms proposed to resolve the issue of human rights violations is through the establishment of a Truth and Reconciliation Commission (TRC). The TRC functions to reveal the truth about past human rights violations, provide opportunities for victims to obtain justice, and encourage the process of social reconciliation. This abstract aims to examine the position of the TRC in the context of resolving human rights violations in Indonesia, both from a legal perspective, its role in recovering victims, and the challenges faced in its implementation. This research also highlights the difference between settlement through the judiciary and settlement through th , as well as the extent to which the TRC can create restorative justice without ignoring applicable legal principles. Through this analysis, it is hoped that a deeper understanding can be obtained regarding the potential and limitations of the TRC mechanism in realizing resolution of human rights violations in Indonesia.